A Semantic Analysis of the Concept of Beauty (Güzellik) in Turkish Language: Mapping the Semantic Domains - Démuth, Andrej; Démuthová, Slávka; Keçeli, Yasin (Frontiers in Communication, 2022)
In this study, we shall attempt to clarify the semantic levels used in ordinary Turkish language when using the concept of beauty. We assume that the concept of beauty represents a multidimensional semantic complex saturated from numerous – often very diverse – dimensions of our perception and judgement. Mapping these fundamental semantic dimensions should thus enable us to then map the semantic space in which the language user operates when they use the notion of beauty. In this work we shall focus on the internal structure, the diversification of the most important semantic domains of the notion of beauty and on the revelation of some of the connections between the particular domains and we shall use the bottom – up approach.